Cuidados de enfermería en la prevención del tromboembolismo venoso en pacientes quirúrgicos: una revisión sistemática - Muñoz Yautibug, Nataly Silvana (2026)
Venous thromboembolism (VTE) represents a serious complication in surgical patients, with high morbimortality. The role of nursing is fundamental in the identification of risks and application of preventive measures. Objective: To protocolize preventive nursing interventions to reduce the risk of VTE in surgical patients, based on scientific evidence published from 2020 and 2025. Materials and methods: A qualitative systematic review was carried out using the PRISMA method for the period 2020 - 2025 in the databases of PubMed, Google Scholar, Scielo, Researchgate, Frontiers, Mdpi, Springer, Wiley and Sciencedirect, identifying 748 articles and selecting 20 studies after applying the inclusion and exclusion criteria. Results: The findings allowed identifying applicable interventions in a nursing protocol such as: Preoperative risk assessment; early mobilization in the immediate postoperative period; use of intermittent pneumatic compression devices; continuous education to the patient and family in all phases of the surgical process; constant monitoring of clinical status with adjustments of prophylactic measures; and post-discharge follow-up to ensure adherence and detect signs of complications. Conclusions: The implementation of a structured protocol strengthens patient safety and quality of care. However, it is necessary to promote clinical studies that validate practices in local contexts.